To solve the equation \(3x - 7 - 2x + 5 = 6\), we can follow these steps:
Step 1: Combine like terms on the left side of the equation.
In this case, combine \(3x\) and \(-2x\), and also \(-7\) and \(+5\).
This gives us:
\( (3x - 2x) + (-7 + 5) = 6 \)
which simplifies to:
\( x - 2 = 6 \)
Step 2: Add 2 to both sides of the equation to isolate the variable \(x\).
This gives us:
\( x - 2 + 2 = 6 + 2 \)
Simplifying this results in:
\( x = 8 \)
Step 3: Confirm the solution by substituting \(x = 8\) back into the original equation.
This checks that the left side equals the right side:
\( 3(8) - 7 - 2(8) + 5 \)
Calculating gives:
\( 24 - 7 - 16 + 5 = 6 \)
which is true.
Final answers:
- Step 1: Combine like terms.
- Step 2: Isolate \(x\).
- Step 3: Verify the solution.
For Question 2, the answer is:
- \( \mathbf{x = 8} \)